Barking Water [videorecording (DVD)] - Harjo, Sterlin; Harjo, Sterlin; Camp-Horinek, Casey; Whitman, Richard Ray; Proudstar, Jon (Lorber Films : Cinema Purgatorio : Distributed by Kino Lorber, Inc., 2010)
Frankie, a proud Native American, is attempting to reconnect with his estranged family. Released from the hospital, but still very ill, he hits the road with his ex-lover Irene, who acts as Frankie's nurse but refuses to offer forgiveness for his past indiscretions. As they travel through the sun-dappled country, they encounter various eccentric personalities. But his journey really begins when he reunites with his daughter and finally meets her newborn child.